Endodontic Considerations in Three-canalled Premolars: A Practical Update - Mohammadi, Zahed (Iran Endod J, 2016)
The most difficult clinical considertions in orthograde root canal treatment are generally related to the anatomy of the teeth. Three-canalled maxillary and mandibular premolars (mini-molars) have been reported in several studies. The purpose of this paper was to review various aspects of three-canalled premolars including incidence, clinical and radiographic diagnosis, racial predisposition, access cavity preparation, instrumentation and obturation.